PERENCANAAN TURBIN AIR MIKRO HIDRO JENIS PELTON UNTUK PEMBANGKIT LISTRIK DI DESA KALI KECAMATAN PINELENG DENGAN HEAD 12 METER - Ceri Steward Poea; Gerits Dirk Soplanit; Jotje Rantung (JURNAL POROS TEKNIK MESIN UNSRAT, 2012)
The utilization of water as a natural resource of renewable energy for power plant is one of the alternative solutions to replace the need for fossil fuels. there is a waterfall on the river which through Kali village in Pineleng district, From observations and the calculation speed of the flow by using buoys, and river cross-sectional area obtained the total river debit Q = 0.323 m3 / s. From the measurements is also obtained high fall the waterfall H = 12 m. Based on the existing height and debit of the water fall the major dimensions of a water turbine Pelton Micro Hydro type as the driving power generator was planned. The results of calculations for effective head = 12 m, with a water debit that is used to drive the runners Q = 0.06 m3/s, gained power generated by 4.0 kW. By the data is planned the main dimensions of micro turbine Pelton outer runner diameter Do = 380.8 mm, the diameter of the circle pin D = 202 ​​mm, number of bowls z = 19 with 1 nozzle, and a shaft diameter ds = 45 mm. Key Word: Kali Village Pineleng, Pelton Water Turbin